Outcomes and moderators of a preventive school-based mental health intervention for children affected by war in Sri Lanka: A cluster randomized trial - Tol, W.A.; Komproe, I.H.; Jordans, M.J.D.; Vallipuram, A.; Sipsma, H.; Sivayokan, S.; MacY, R.D.; De Jong, J.T. (My University, 2012)
We aimed to examine outcomes, moderators and mediators of a preventive school-based mental health intervention implemented by paraprofessionals in a war-affected setting in northern Sri Lanka. A cluster randomized trial was employed. Subsequent to screening 1,370 children in randomly selected schools, 399 children were assigned to an intervention (n=199) or waitlist control condition (n=200). The intervention consisted of 15 manualized sessions over 5 weeks of cognitive behavioral techniques and creative expressive elements. Assessments took place before, 1 week after, and 3 months after the intervention. Primary outcomes included post-traumatic stress disorder (PTSD), depressive, and anxiety symptoms. No main effects on primary outcomes were identified. A main effect in favor of intervention for conduct problems was observed. This effect was stronger for younger children. Furthermore, we found intervention benefits for specific subgroups. Stronger effects were found for boys with regard to PTSD and anxiety symptoms, and for younger children on pro-social behavior. Moreover, we found stronger intervention effects on PTSD, anxiety, and function impairment for children experiencing lower levels of current war-related stressors. Girls in the intervention condition showed smaller reductions on PTSD symptoms than waitlisted girls. We conclude that preventive school-based psychosocial interventions in volatile areas characterized by ongoing war-related stressors may effectively improve indicators of psychological wellbeing and posttraumatic stress-related symptoms in some children. However, they may undermine natural recovery for others. Further research is necessary to examine how gender, age and current war-related experiences contribute to differential intervention effects.
Keywords: Anxiety; Armed conflict; Depression; Political violence; Post-traumatic stress disorder; Prevention; School-based intervention; Sri Lanka